High resolution inclination records from the Gulf of Alaska, IODP Expedition 341 Sites U1418 and U1419. Issue 1 (26th November 2021) - Velle, Julie Heggdal; Walczak, Maureen H; Reilly, Brendan; St-Onge, Guillaume; Stoner, Joseph S; Fallon, Stewart; Mix, Alan C; Belanger, Christina; Forwick, Matthias
SUMMARY: International Ocean Drilling Program (IODP) Expedition 341 recovered sediments from the south Alaska continental slope that preserves a well resolved and dated inclination record over most of the past ∼43 000 yr. The Site U1419 chronology is among the highest resolution in the world, constrained by 173 radiocarbon dates, providing the ability to study Palaeomagnetic Secular Variation (PSV) on centennial to millennial timescales. This record has an exceptionally expanded late Pleistocene sedimentary record with sedimentation rates commonly exceeding 100 cm kyr –1, while also preserving a lower resolution Holocene PSV record at the top. Natural and laboratory-induced magnetic remanences of U1419 u-channels from the 112-m-long spliced record were studied using stepwise AF demagnetization. Hysteresis loops were obtained on 95 and IRM acquisition curves on 9 discrete samples to facilitate magnetic domain state, coercivity and magnetic mineralogical determinations. Due to complexities related to lithology, magnetic mineralogy, and depositional and post-depositional processes, Site U1419 sediments are not suitable for palaeointensity studies and declination could not be robustly reconstructed. Progressive (titano-)magnetite dissolution with depth results in decreasing NRM intensity and signal-to-noise that is exacerbated at higher demagnetization steps. As a result, inclination measured after the 20 mT AF demagnetization step provides the most reliable directional record. Inclination appears to be well resolved with removal of just a few intervals influenced by depositional and/or sampling and coring deformation. The shipboard inclination stack from nearby IODP Site U1418, on a new age model developed from 19 radiocarbon dates on U1418 and 18 magnetic susceptibility-based tie-points to site survey core EW0408-87JC, verifies centennial to millennial scale variations in inclination observed in U1419. Comparisons with other independently dated records from the NE Pacific and western North America suggest that these sites likely capture regional geomagnetic variability. As such, this new high-resolution and well-dated inclination record, especially robust between 15 and 30 cal kyr BP, offers new geomagnetic insights and a regional correlation tool to explore this generally understudied part of the world.